Eosinophil-expressed galectin-3 regulates cell trafficking and migration - Ge, Xiao Na; Ha, Sung Gil; Liu, Fu-Tong; Rao, Savita P.; Sriramarao, P (Frontiers in Pharmacology, 2013)
Galectin-3 (Gal-3), a β galactoside-binding lectin, is implicated in the pathogenesis of allergic airway inflammation and allergen-challenged mice deficient in Gal-3 (Gal-3-/-) exhibit decreased airway recruitment of eosinophils (Eos). Gal-3 is expressed and secreted by several cell types and can thus function extracellularly and intracellularly to regulate a variety of cellular responses. We sought to determine the role of Eos-expressed Gal-3 in promoting Eos trafficking and migration in the context of allergic airway inflammation using bone marrow (BM)-derived Eos from wild-type (WT) and Gal-3-/- mice. Airway recruitment of Eos in acute (4 weeks) and chronic (8–12 weeks) allergen-challenged WT mice correlated with Gal-3 expression in the lungs. BM-derived Eos were found to express Gal-3 on the cell surface and secrete soluble Gal-3 when exposed to eotaxin-1. Compared to WT Eos, Gal-3-/- Eos exhibited significantly reduced rolling on vascular cell adhesion molecule 1 (VCAM-1) and decreased stable adhesion on intercellular adhesion molecule 1 (ICAM-1) under conditions of flow in vitro. Evaluation of cytoskeletal rearrangement demonstrated that relatively fewer adherent Gal-3-/- Eos undergo cell spreading and formation of membrane protrusions. In addition, cell surface expression of integrin receptor αM (CD11b) was lower in Gal-3-/- Eos, which is likely to account for their altered adhesive interactions with VCAM-1 and ICAM-1. Gal-3-/- Eos also exhibited significantly decreased migration toward eotaxin-1 compared to WT Eos irrespective of similar levels of CCR3 expression. Further, eotaxin-induced migration of WT Eos remained unaffected in the presence of lactose, suggesting a role for intracellular Gal-3 in regulating Eos migration. Overall, our findings indicate that Gal-3 expression in the lungs correlates with Eos mobilization during allergic airway inflammation and signaling involving intracellular Gal-3 and/or secreted Gal-3 bound to the cell surface of Eos appears to be essential for Eos trafficking under flow as well as for migration.